B-1b Cells Have Unique Functional Traits Compared to B-1a Cells at Homeostasis and in Aged Hyperlipidemic Mice With Atherosclerosis - Srikakulapu, Prasad; Pattarabanjird, Tanyaporn; Upadhye, Aditi; Bontha, Sai Vineela; Osinski, Victoria; Marshall, Melissa A.; Garmey, James; Deroissart, Justine; Prohaska, Thomas A.; Witztum, Joseph L.; Binder, Christoph J.; Holodick, Nichol E.; et al. (Frontiers in Immunology, 2022)
Immunoglobulin M (IgM) to oxidation specific epitopes (OSE) are inversely associated with atherosclerosis in mice and humans. The B-1b subtype of B-1 cells secrete IgM to OSE, and unlike B-1a cells, are capable of long-lasting IgM memory. What attributes make B-1b cells different than B-1a cells is unknown. Our objectives were to determine how B-1b cells produce more IgM compared to B-1a cells at homeostatic condition and to see the differences in the B-1a and B-1b cell distribution and IgM CDR-H3 sequences in mice with advanced atherosclerosis. Here, in-vivo studies demonstrated greater migration to spleen, splenic production of IgM and plasma IgM levels in ApoE-/-Rag1-/- mice intraperitoneally injected with equal numbers of B-1b compared to B-1a cells. Bulk RNA seq analysis and flow cytometry of B-1a and B-1b cells identified CCR6 as a chemokine receptor more highly expressed on B-1b cells compared to B-1a. Knockout of CCR6 resulted in reduced B-1b cell migration to the spleen. Moreover, B-1b cell numbers were significantly higher in spleen of aged atherosclerotic ApoE-/- mice compared to young ApoE-/- mice. Single cell sequencing results of IgHM in B-1a and B-1b cells from peritoneal cavity and spleen of atherosclerotic aged ApoE-/- mice revealed significantly more N additions at the V-D and D-J junctions, greater diversity in V region usage and CDR-H3 sequences in B-1b compared to B-1a cells. In summary, B-1b cells demonstrated enhanced CCR6-mediated splenic migration, IgM production, and IgM repertoire diversification compared to B-1a cells. These findings suggest that potential strategies to selectively augment B-1b cell numbers and splenic trafficking could lead to increased and more diverse IgM targeting OSE to limit atherosclerosis.